Faktor Faktor Yang Mempengaruhi Terjadinya Infeksi Saluran Kemih - Sekar Feni Widiyastuti; Tri Umiana Soleha (CV. Jasa Sukses Abadi, 2023)
Urinary tract infection (UTI) is a collective term that describes any infection that involves any part of the urinary tract, include the kidneys, ureters, bladder and urethra. Urinarytract infection is also usually defined as an increase in the number of bacteria limiting 105 CFU or more, with symptoms such as frequent urge to urinate, pain, dysuria. Urinary tract infections can be caused by various types of bacteria. The bacteria that cause urinary tract infections are Escheria coli, Klebsiella sp, Proteus sp, Providensia, Citrobacter, Pseudomonas aeruginosa, Acinetobacter, Enterococsu faecali and Staphylococcus saprophyticus, Staphylococcus aureus, however, the leading cause of UTIs is generally caused by Escheria coli. There are many factors that influence the occurrence of urinary tract infections. The purpose of this literature review is to analyze the etiology and factors that influence the occurrence of UTI. The literature review was carried out through electronic-based journals, namely the Proquest database and Google Schola. The literature used is in accordance with the keywords, namely factors that influence the incidence of UTI. The inclusion criteria were articles published maximum in 2013. Meanwhile, the exclusion criteria were literature published in 2012 and below. Based on the research results obtained regarding. factors that influence the occurrence of urinary tract infections such as female gender, old age, catheter insertion, genital hygiene, comorbid diseases such as diabetes mellitus, hypertension, cerebrovascular disease and general health conditions.